STUDI LITERATUR TENTANG KENAKALAN REMAJA - Aryani, Anisa Sri; Rosmawati, Rosmawati; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The study was carried out to identify the basic concepts and theories, factors and efforts to deal with delinquency. The kind of research used was literature studies. The instruments used in this study are a combination of national journals and international journals. Anaisis data in the study for content analysis. Studies have shown that delinquency can be characterized by the behavior of some youths that is contrary to the laws, religion and norms of society, which can harm others, destabilize public order as well as damage itself. As for the factors that affect that are internal and external factors that are present in young students. So the effort it can make to address delinquency is to do some (1) preventive measures, (2) repressive measures, and (3) curative and rehabilitation measures.Key Words: Literature Study, Juvenile Delinquency